IRRITABLE BOWEL SYNDROME (Homoeopathy for All, 2023)
Irritable bowel syndrome (IBS) is a  chronic and debilitating functional  gastrointestinal disorder that affects 9%-23% of the population  across the world. IBS is a disorder  of the movement of the intestines,  the sensitivity of the nerves of the  intestines, or how the brain controls  some of these functions. It was  p r e v i o u s l y k n o w n a s a gastrointestinal disorder. In this  disability, and economic non-productivity. As the pathophysiology of IBS  is poorly understood, the management generally focuses on the  amelioration of symptoms and improvement in the quality of life. At  present, the drugs available for the treatment of IBS have only a modest  effect on symptom improvement and may not alter the natural history of  the condition.
Keywords: debilitating; symptoms; management